Fast determination of lignocellulosic composition of poplar biomass by thermogravimetry. (March 2019) - Rego, Filipe; Soares Dias, Ana P.; Casquilho, Miguel; Rosa, Fátima C.; Rodrigues, Abel
Abstract: The evaluation of the amount of lignocellulosic polymeric components of woody biomass is fundamental to assess its adequacy to produce energy or chemicals. Classic techniques for quantification of these components are slow and laborious, and modern expeditious techniques such as thermogravimetry (TG) have allowed for new and accurate measurement methodologies. TG was used to analyze woody biomass and lignocellulosic composition was assessed through deconvolution of rate of mass loss curves with a pseudo-component model. The quantification of hemicelluloses, cellulose and lignin was performed for nine different poplar genotypes grown as a short rotation coppice (SRC) in Portugal and Belgium. The average composition was (% mass, dry basis) 23% hemicelluloses, 49% cellulose and 27% lignin, with the remaining 1% ash. The classic determination of lignin (Klason) allowed to comparable content (29%). Moreover, TG results agree with published data obtained by conventional wet techniques for poplar wood. The usefulness of the application of TG for lignocellulosic content determination was verified, allowing useful and simple characterization of biomass for thermochemical conversion processes. SRCs are envisaged as an auspicious renewable source of woody biomass, and TG can be a valuable tool to improve the knowledge of factors related to the influence of genetic and environmental conditions on biomass quality. Graphical abstract: Image 1 Highlights: Thermogravimetry (TG-DTG) was used for characterization of poplar biomass. Moisture, hemicellulose, cellulose and lignin were assessed by a single TG test. DTG profiles were deconvoluted using Gauss curves to compute mass fractions. TG Lignin content was comparable to Klason classic determination. TG is a fast and accurate method for lignocellulosic content evaluation.